Nature tourism in Peneda-Gerês National Park (Portugal): tourism motivation and strategic planning - Fernandes, Bruno Miguel (2021)
The increase in demand at the Peneda-Gerês National Park (PNPG), the first protected area created and the only national park in Portugal, demonstrates the growing interest in nature and adventure tourism, both national and international, also confirming current trends in today´s society. However, this research implies the definition of strategies that aim at the protection, conservation and sustainability of the territory, within the scope of tourism development. In this article, a qualitative analysis was carried out based on semi-structured interviews with two managers from two key entities of the territory, focusing on tourism supply and demand in the region, in order to understand what has already been implemented, what is in development and which are aimed at addressing the urgencies observed in the territory. According to the interviewees, there are problems related to the massification of tourism in the region and the seasonality of tourism demand, caused in a way by the lack of information about the park, both from an internal point of view (human resources training) as external (provision of necessary information for tourists). Also highlighted were the weak infrastructures and the difficult accesses, as well as the lack of investment and entrepreneurship in the PNPG. For those reasons, strategic actions must continue to be implemented, and new strategies must be developed in order to boost economic development of the territory and to offer quality, safe, diversified and sustainable tourism.